Eyes on Customary Forests Transition of Traditional Forests into Production Forests - Wahyu RAMADAI, Eko; SALMA, Qorin Anida; Fitria CAHYANI, Adinda Agis (Protection: Journal Of Land And Environmental Law, 2024)
Forests as a medium for balancing nature are something whose importance cannot be ignored in human life and civilization. Forests must be managed, protected, and utilized sustainably for the community's welfare, both current and future generations. The problem of customary forests in Indonesia tends to be paradoxical; constitutionally, it has been regulated so that matters are aimed at providing justice, certainty and benefits for indigenous peoples and customary forests. However, Indonesia is known as "The Scramble For Land Rights," where there is a gap between companies and customary law communities in terms of getting opportunities for land tenure rights. This research uses a normative method with a statutory approach, which is expected to answer the problem of how customary forests become production forests in Indonesia and how customary forests become production forests in Indonesia are transitioned from the perspective of justice, certainty and benefit. The current problem is related to permits given unilaterally by indigenous people to companies. Apart from that, the issue of legal action for permit violations is currently not being carried out properly, so many customary forests are still being "grabbed" by companies and not heeding legal regulations by statutory regulations. Constitutionally, the status of customary law is guaranteed. However, law enforcement in the field and supervision from related parties are minimal, causing many problems in transitioning customary forests to production forests.